Novel homozygous inactivating mutation of the calcium-sensing receptor gene (CASR) in neonatal severe hyperparathyroidism-lack of effect of cinacalcet - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP (ELSEVIER SCIENCE INC, 2014)
Background: NSHPT is a life-threatening disorder caused by homozygous inactivating calcium-sensing receptor (CASR) mutations. In some cases, the CaSR allosteric activator, cinacalcet, may reduce serum PTH and calcium levels, but surgery is the treatment of choice. Objective: To describe a case of NSHPT unresponsive to cinacalcet. Patient and Results: A 23-day-old girl was admitted with hypercakemia, hypotonia, bell-shaped chest and respiratory distress. The parents were first-degree cousins once removed. Serum Ca was 4.75 mmol/l (N: 2.10-2.62), P: 0.83 mmol/l (1.55-2.64), PTH: 1096 pg/ml (9-52) and urinary Ca/Cr ratio: 0.5 mg/mg. First, calcitonin was given (10 IU/kg x 4/day), and then 2 days later, pamidronate (0.5 mg/kg) for 2 days. Doses of cinacalcet were given daily from day 28 of life starting at 30 mg/m(2) and increasing to 90 mg/m(2) on day 43. On day 33, 6 days after pamidronate, serum Ca levels had fallen to 2.5 mmol/l but, thereafter, rose to 5 mmol/l despite the cinacalcet Total parathyroidectomy was performed at day 45. Hungry bone disease after surgery required daily Ca replacement and calcitriol for 18 days. At 3 months, the girl was mildly hypercalcemic, with no supplementation, and at 6 months, she developed hypocalcemia and has since been maintained on Ca and calcitriol. By CASR mutation analysis, the infant was homozygous and both parents heterozygous for a deletion-frameshift mutation. Conclusion: The predicted nonfunctional CaSR is consistent with lack of response to cinacalcet, but total parathyroidectomy was successful. An empiric trial of the drug and/or prompt mutation testing should help minimize the period of unnecessary pharmacotherapy. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Neonatal severe hyperparathyroidism; Calcium-sensing receptor; Mutation; Calcimimetic; FAMILIAL HYPOCALCIURIC HYPERCALCEMIA; PAMIDRONATE; RESCUE